The Influence of Pt Atomic Ratio in the Activity PtNi/C Nanocatalysts for the PEMFC - Rusnaeni, Nenen; Purwanto W., Widodo; Nasikin, Mohammad; Hendrajaya, Lilik (ITB Journal Publisher, LPPM ITB, 2011)
Pt-Ni/C alloy nanocatalysts synthesized by polyol method with different atomic ratio are investigated to enhance activity of the oxygen reduction reaction (ORR) for fuel cell applications. Prepared catalysts are characterized by various techniques, such as X-ray diffraction (XRD), scanning electron microscopy (SEM-EDX), and cyclic voltammetry (CV). XRD analysis shows that all prepared catalysts with different atomic ratio exhibit face centered cubic and have smaller lattice parameters than pure Pt catalyst. The mean particle size of the catalysts are between 4.3 to 6.3 nm. Cyclic voltammograms with scan rate 5 mV s-1 at 25oC obtain range the electrochemical active surface (EAS) between 40 to 164 cm2/mgPt, mass activity (MA) and specific activity (SA) of nanocatalysts PtNi/C in the potential range 900 mV versus RHE between 3.61 to 8.42 mA/mgPt, and 0.05 to 0.09.